Dramatic Aspirations at Villa Borghese: The Theatrics of Bernini's Sculptural Group - Peterson, Olivia (My University, 2019)
This paper focuses on both the display and subject matter of Gian Lorenzo Bernini’s sculptures at Villa Borghese in Rome, Italy. Utilizing research with primary source material, including biographical accounts of Bernini’s life, evidence of the artist’s interest and involvement in the theater of the seventeenth century is illuminated. The sculptural group at the villa exemplifies Bernini’s early affinity for theatricality within the context of the larger Borghese collection. This is explored through examination of the sculptures’ compositional arrangement, placement within the gallery, and visual presentation of emotion. Each aspect encourages viewer interaction with the sculptures, much like that which is achieved during musical and theatrical performances from the same time period. Delving into art theory and criticism from the time period, Bernini’s approach to the sculptures featured at Villa Borghese is a testament to the artist’s ability to evoke viewer response to his work. This paper will look in detail at one of the four main sculptural groups of the villa. This sculpture, Apollo and Daphne, will be analyzed visually and in reference to pertinent literature in order to explore its similarity of presentation to visual performances of the theater in the seventeenth century.
Keywords: Villa Borghese; Baroque; Theater; Apollo; Daphne; Bernini